Prognostic implication of hepatoduodenal ligament lymph nodes in gastric cancer. Issue 13 (March 2017) - Oh, Sung Eun; Choi, Min-Gew; Lee, Jun Ho; Sohn, Tae Sung; Bae, Jae Moon; Kim, Sung
Abstract : Abstract: There has been controversy regarding whether hepatoduodenal lymph node (HDLN) metastasis in gastric cancer is distant or regional metastasis. HDLN positivity was classified as distant metastasis in the 7th American Joint Committee on Cancer (AJCC) classification, but it was reclassified as regional lymph node metastasis in the 8th AJCC classification. The aim of our study is to verify prognostic significance of HDLN metastasis in gastric cancer. This retrospective study enrolled patients with gastric cancer who underwent D2 gastrectomy from January 2007 to June 2010. HDLN was classified as a regional lymph node. Total number of patients was 3175; 143 (4.5%) of them had HDLN metastasis. The HDLN positivity was significantly associated with older age, more advanced tumor stage, undifferentiated histologic type, and pathologic diagnosis of lymphatic, vascular, and perineural invasions. Five-year survival rate of HDLN-positive patients with stages I to III disease was significantly higher than that of stage IV group (59.3% vs 18.8%, P = 0.001). In patients with stage III disease, 5-year survival rate of HDLN-positive group was significantly lower than that of HDLN-negative group (51.7% vs 66.3%, P = 0.001). Multivariate analysis showed that HDLN metastasis was an independent prognostic factor. HDLN has a different prognostic significance from other regional lymph nodes in advanced stage of gastric cancer though its positivity is not considered as distant metastasis. HDLN positivity itself seems to be an independent prognostic factor in gastric cancer, and the survival outcomes of patients with stage III disease need to be reconsidered according to HDLN positivity.